CHRISTIAN MISSIONARIES' ACTIVITIES DURING THE COLONIAL ERA: AN OVERVIEW - Sharan S J (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study examines the evolution of Christian missionary activities in colonial India and their enduring legacy in modern Indian society. Initially focused on religious conversion, missionary efforts gradually expanded to include education, healthcare, and social reforms, profoundly influencing India’s social and intellectual landscape. Missionaries played a pivotal role in establishing educational institutions and hospitals, promoting literacy, social equality, and the rights of marginalised communities. Their advocacy for reforms such as the abolition of Sati and widow remarriage contributed to India’s broader social justice movements. Additionally, the Western ideals introduced by missionaries helped shape the intellectual foundations of Indian nationalism and the fight for independence. The modern implications of missionary work are seen in the continued operation of missionary-founded institutions, the hybridisation of religious and cultural practices, and ongoing debates around conversion and religious pluralism. This study also highlights the need for further research into the multifaceted legacy of missionary activities in India.